Photochemical Treatments of Textile Industries Wastewater - Hassan Hussein, Falah (Asian Journal of Chemistry, 2012)
Textile industry is one of the most water and chemical intensive industries worldwide. About 200-400 L of water are needed to produce 1 kg of textile fabric in textile factories. The water used in this industry is almost entirely discharged as waste. Moreover, the lost of dye in the effluents of textile industry can reach up to 50 %. The effluents are very complex, containing salt, surfactants, ionic metals and their metal complexes, toxic organic chemicals, biocides and toxic anions. Semiconductors are used to degrade pollutants in water to less harmful inorganic material. There have been numerous studies carried out across the globe focusing on the decolourization of textile wastewater. The importance of these types of research is being increasingly in the recent and has become a subject of major public health concern and scientific interest. Titanium dioxide and zinc oxide have good photocatalytic properties nominated both catalysts to be promising substrates for photodegradation of water pollutants and show the appropriate activity in the range of solar radiation. Recent studies focused on the most important photocatalytic applications of titanium dioxide and zinc oxide. These applications include the photodegradation of various pollutants killing bacteria and killing tumor cell in cancer treatments. In recent years there is a substantial interest in decolourization of industrial wastewater, especially textile wastewater. Textile industry generates large quantities of wastewater and also regarded as very toxic due to the difficulty of its disrobement by physical, chemical and microbiological methods. The overall benefits of the decolourization of textile industrial wastewater may include very interesting subjects, saving a huge amount of water and minimizing environmental pollutions. The treated water may be recycled in the same factory or reused in other applications such as other industries or agriculture that require a less quality water. This is considered to be very excellent means for saving huge amounts of water, especially, in the countries which are suffered with water deficiency. This work will describe some of the more common features of textile industrial wastewater and the evaluation of the treated wastewater by using titanium dioxide and zinc oxide to judge the validity of this type of water for using in different fields.